PRIMEIRO RELATO DE Puccinia lantanae EM ERVA-CIDREIRA-BRAVA NO MATO GROSSO DO SUL - Gomes Cavalcanti , Vittor; Fernandes da Costa , Brenda; André Sganzerla Graichen , Felipe; Henrique Martinez Blanco , Neder; de Souza da Silva, Talísia; Idelfonso Oliveira , Thaliata (ANAIS DO ENIC, 2026)
-